Validation of flood risk models: Current practice and possible improvements. (February 2019) - Molinari, Daniela; De Bruijn, Karin M.; Castillo-Rodríguez, Jesica T.; Aronica, Giuseppe T.; Bouwer, Laurens M.
Abstract: Although often neglected, model validation is a key topic in flood risk analysis, as flood risk estimates are used to underpin large investments and important decisions. In this paper, we discuss the state of the art of flood risk model validation, using as input the discussion among more than 50 experts at two scientific workshop events. The events aimed at identifying policy and research recommendations towards promoting more common practice of validation, and an improvement of flood risk model reliability. We pay specific attention to different components of the risk modelling chain (i.e. flood hazard, defence failure, and flood damage analysis) as well as to their role in risk estimates, to highlight specificities and commonalities with respect to implemented techniques and research needs. The main conclusions from this analysis can be summarised as the need of higher quality data to perform validation and of benchmark solutions to be followed in different contexts, along with a greater involvement of end-users in the application on flood risk model validation.